Communication Strategies In Strengthening Resilience Towards A Sustainable Future Learning From The Covid-19 Pandemic - Imran Kahar (Universitas Padjadjaran, 2022)
The purpose of this writing is to see if communication strategies play a role in strengthening resilience towards a sustainable future by learning from the covid-19 pandemic. The method used is a qualitative method by looking at the relationship of communication strategies in strengthening resilience towards a sustainable future This research is for the creation of proper communication between government and society based on accurate information. So it is expected that this study provides recommendations and understanding of the importance of communication strategies in strengthening resilience towards a sustainable future in order to learn from the current Covid-19 pandemic.